2020
DOI: 10.1080/02513625.2020.1906059
|View full text |Cite
|
Sign up to set email alerts
|

Urban Sustainability Versus the Impact of Covid-19

Abstract: Most recent research on urban health has primarily been focused on non-communicable diseases related to sedentary lifestyles, unbalanced diets and the high concentration of pollutants derived from anthropogenic activities. Cardiovascular and respiratory diseases, heatstroke and cold-related problems and injuries and accidents due to road traffic were some of the main public health challenges over several decades (HUDU 2007), which aligned perfectly with Sustainable Development Goals #3 (Health and Wellbeing), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Vulnerability was a major factor in the first waves of the COVID-19 pandemic ( Almagro and Orane-Hutchinson, 2022 ; Nathan, 2021 ). In Madrid, the inner suburbs saw more pandemic cases ( Glodeanu et al, 2021 ; Gómez Giménez, 2020 ; Marí-Dell’Olmo et al, 2021 ; Menéndez and Higueras García, 2020 ). Different justifications have rationalised this geographical pattern of COVID-19 impact.…”
Section: The Development Of Vulnerable Inner Suburbs and The Impact O...mentioning
confidence: 99%
See 3 more Smart Citations
“…Vulnerability was a major factor in the first waves of the COVID-19 pandemic ( Almagro and Orane-Hutchinson, 2022 ; Nathan, 2021 ). In Madrid, the inner suburbs saw more pandemic cases ( Glodeanu et al, 2021 ; Gómez Giménez, 2020 ; Marí-Dell’Olmo et al, 2021 ; Menéndez and Higueras García, 2020 ). Different justifications have rationalised this geographical pattern of COVID-19 impact.…”
Section: The Development Of Vulnerable Inner Suburbs and The Impact O...mentioning
confidence: 99%
“…Different justifications have rationalised this geographical pattern of COVID-19 impact. Characteristics of the built environment, including a scarcity of green areas ( Menéndez and Higueras García, 2020 ) and small dwelling size ( Gómez Giménez, 2020 ), partially explained the impact of the pandemic in vulnerable neighbourhoods. As in other contexts ( McFarlane, 2021 ), density was not a key factor.…”
Section: The Development Of Vulnerable Inner Suburbs and The Impact O...mentioning
confidence: 99%
See 2 more Smart Citations
“…It also showed that city spatial structures based on mono functionality and separation lead to a faster spread of pathogens than the model based on dispersed areas of human activity. Research conducted in Madrid (Menéndez & Higueras García, 2020) and Porto (da Silva Lopes et al, 2021) during the Covid-19 pandemic has shown an accelerated loss of traditional service functions by city centres, especially those targeting global tourism. These studies highlighted the need to deepen the analysis in the context of the polycentric development of urban structures.…”
Section: Influence Of City Structure On Development Changes In the Smart Citymentioning
confidence: 99%